2014
DOI: 10.1093/cercor/bhu063
|View full text |Cite
|
Sign up to set email alerts
|

Reflections of Oneself: Neurocognitive Evidence for Dissociable Forms of Self-Referential Recollection

Abstract: Research links the medial prefrontal cortex (mPFC) with a number of social cognitive processes that involve reflecting on oneself and other people. Here, we investigated how mPFC might support the ability to recollect information about oneself and others relating to previous experiences. Participants judged whether they had previously related stimuli conceptually to themselves or someone else, or whether they or another agent had performed actions. We uncovered a functional distinction between dorsal and ventr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 55 publications
(103 reference statements)
5
33
0
Order By: Relevance
“…In addition to enhanced memory for objects belonging to the similar other, we also observed biased errors in ownership judgment indicating greater confusion between self/similar target than self/dissimilar target -as was reported by Benoit et al (2010) and Bergstrom et al (2015) using source memory (for target, self vs. other) for character trait adjectives. So our present findings confirm, using a different SRE paradigm, that simulating similar others can lead to source confusion.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…In addition to enhanced memory for objects belonging to the similar other, we also observed biased errors in ownership judgment indicating greater confusion between self/similar target than self/dissimilar target -as was reported by Benoit et al (2010) and Bergstrom et al (2015) using source memory (for target, self vs. other) for character trait adjectives. So our present findings confirm, using a different SRE paradigm, that simulating similar others can lead to source confusion.…”
Section: Discussionsupporting
confidence: 69%
“…predicts) subsequent memory for these stimuli . The finding was replicated by Benoit, Gilbert, Volle, and Burgess (2010) , and recently by Bergstrom. Vogelsang, Benoit, and Simons (2015), who showed that regions within ventral mPFC are also differentially active during retrieval of stimuli related to self vs. other controls.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Time and dispersion derivatives were included for each event and each parametric modulator. The 8 separate scan blocks were concatenated for analysis to obtain more stable parameter estimates due to increasing the number of trials per condition, as is often the case for designs splitting trials by performance (Uncapher et al, 2006; Bergström et al, 2015). As runs were concatenated, standard high pass filtering using SPM was not possible, as SPM would treat the runs as one continuous time-series.…”
Section: Methodsmentioning
confidence: 99%
“…The stronger co-activation among these regions when retrieving AMs from OE perspectives likely contributed to higher subjective ratings of vividness when compared to OB perspectives. We also found co-activation between the anterior hippocampus and ventromedial PFC, a region linked to conceptual aspects of self-reference and affective value (e.g., Bergstrom and others 2015; Lin and others 2016) that enable the formation of abstract mental models or schemas about the world and oneself in order to extract meaning to guide behavior (for reviews see D’Argembeau 2013; Gilboa and Marlatte 2017; Morton and others 2017; Roy and others 2012). During retrieval, interactions between the ventromedial PFC and the anterior hippocampus are thought to contribute to updating of reactivated memories guided by abstract memory representations (Schlichting and Preston 2015), which may contribute to the transformation of memories overtime (Moscovitch and others 2016).…”
Section: Discussionmentioning
confidence: 81%